Unraveling the Brain Drain Dilemma: Analysis among Skilled Information Technology Professionals of Nepal - Jha, Baby Kumari; Thakur, Rashmi; Nepal, Ananda; Chhetri, Surya; Bhandary, Bhushan (Apex Journal of Business and Management, 2024)
This research explores the phenomenon of brain drain among skilled IT professionals in Nepal, aiming to understand the factors influencing their migration decisions. In a globalized context, the study focuses on the challenges faced by Nepal’s IT workforce and their motivations for migration. Using a robust methodology with 185 IT professionals, a multiple regression model is applied, incorporating variables like Employment Prospects, Economic Uplifts, Education, and Personal Ambition, with Brain Drain as the dependent variable. Linear regression’s simplicity is chosen for clarity. Significant correlations between these variables and Brain Drain are found, supported by strong Pearson correlation coefficients. Four hypotheses confirm the impact of Employment Prospects, Economic Uplifts, Education, and Personal Ambition on Migration Intention. The study underscores the financial factors’ dominant role in migration patterns within the IT industry, offering valuable insights for policymakers and industry leaders to formulate targeted strategies for talent retention. This research advocates for further discourse on the multifaceted challenges of brain drain, promoting informed decision-making and effective interventions for the sustainable growth of Nepal’s IT sector.